2000
DOI: 10.2134/agronj2000.92130x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Kentucky Bluegrass Pasture Grazed at Three Heights and Two Intensities

Abstract: Sward height before grazing and amount of forage harvested affect production, composition, and utilization of rotationally stocked pasture. In this 3‐yr field study, yearling steers (Bos taurus L.) grazed 400‐m2 plots of Kentucky bluegrass (Poa pratensis L.)–white clover (Trifolium repens L.) pastures every time sward height reached either 11.8 cm (short), 13.7 cm (medium), or 15.3 cm (tall). Plots were grazed with enough steers to remove either 50 or 60% (grazing intensity) of the herbage mass in 4 h. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…In the summer (second to fourth simulated grazing events), no differences in forage yield were seen among treatments at either site. These data are consistent with results from Inyang et al (2010) and Bryan et al (2000) who demonstrated pasture grasses grazed or clipped to shorter heights had 21 and 18% higher yield throughout the season when managed for taller residual heights. While the highest overall yield would result from grazing to 5 cm, typical MiRG grazing heights recommended are 10 cm .…”
Section: Plumeless Thistle Total ------------------------------------supporting
confidence: 90%
“…In the summer (second to fourth simulated grazing events), no differences in forage yield were seen among treatments at either site. These data are consistent with results from Inyang et al (2010) and Bryan et al (2000) who demonstrated pasture grasses grazed or clipped to shorter heights had 21 and 18% higher yield throughout the season when managed for taller residual heights. While the highest overall yield would result from grazing to 5 cm, typical MiRG grazing heights recommended are 10 cm .…”
Section: Plumeless Thistle Total ------------------------------------supporting
confidence: 90%
“…Many studies of temperate grazing systems reported significant year × treatment effects on pasture parameters, including canopy structure, production, NDF and crude protein (Popp et al, 1997b;Paine et al, 1999;Bryan et al, 2000;Brink et al, 2007). Some of the main conclusions from an extensive study of Wisconsin grazing farms were that 1) forage production and quality were very responsive to fluctuations in weather conditions and these fluctuations interacted with management, resulting in significant differences between years, and 2) while forage quality under rotational vs. continuous grazing was generally higher, it was less predictable (Paine et al, 1999).…”
Section: Implications For Managementmentioning
confidence: 99%
“…The contrasting modes of reproduction facilitate the high polyploidy levels and unusual chromosome numbers (x = 7, 2n = 28-147) observed in P. pratensis (Speckmann and van Dijk, 1972). P. pratensis shows persistence and resilience to cold and seasonal drought (Kanneganti and Kaffka, 1995) and good performance under frequent and close defoliation (Bryan et al, 2000;Durr et al, 2005). Contemporary fructan research is mainly focused on a few plant species including barley, wheat and ryegrass, and despite being a type species for the grass family (Poaceae), little is known about the fructan metabolism in P. pratensis.…”
Section: Introductionmentioning
confidence: 99%